The analgesic and anti-inflammatory activities of the hydroalcholic extract of "Shirishadi compound" in animal model - Divya Kajaria, J.S. Tripathi, S.K.Tiwari, B.L. Pandey (Journal of Applied Pharmaceutical Science)
The main objective of the present investigation is to evaluate the anti-inflammatory & analgesic activity of ethanolic extract of Shirishadi polyherbal compound on rats. Shirishadi compound consist of three herbal drugs namely- Shirisha (Albizzia lebbeck), Nagarmotha (Cyprus rotandus) & Kantakari (Solanum xanthocarpum).In Ayurveda (ancient Indian system of medicine) all these herbs alone or in combination with other herbs are commonly used in the managmant of bronchial asthma. In the carrageenan-induced rat paw edema test for acute inflammation, the extract of Shirishadi compound in doses of 50mg, 200 mg and 500 mg/kg body weight showed 77% and 79% and 81% inhibition of edema, respectively, at the end of 4h which is comparable to that of standard ( endomethacin) i.e. 92%. In the acetic acid induced writhing test the extract of Shirishadi compound (200 and 500 mg/kg body weight) showed a significant (p
Keywords: Shirisadi polyherbal compound,Anti-inflammatory activity,Analgesic activity,Radiant heat tail-flick test,Writhing test.